Measurement of neutrino velocity with the MINOS detectors and NuMI neutrino beam - Adamson, P; Andreopoulos, C; Arms, K; Armstrong, R; Auty, D; Avvakumov, S; Ayres, D; Baller, B; Barish, B; Jr, B; Barr, G; Barrett, W; et al. (2007)
The velocity of a ∼3GeV neutrino beam is measured by comparing detection times at the near and far detectors of the MINOS experiment, separated by 734 km. A total of 473 far detector neutrino events was used to measure (v-c)/c=5.1±2.9×10-5 (at 68% C.L.). By correlating the measured energies of 258 charged-current neutrino events to their arrival times at the far detector, a limit is imposed on the neutrino mass of mν<50MeV/c2 (99% C.L.). © 2007 The American Physical Society.